PEMBERDAYAAN MASYARAKAT DESA GELARWANGI KECAMATAN CIDAUN KABUPATEN CIANJUR MELALUI BUDIDAYA IKAN BAWAL - Iis; Agus Hasbi Noor; Ema Aprianti (IKIP Siliwangi, 2026)
Gelarwangi Village has sufficient potential in the field of aquaculture, for example, there is a lot of land that can be used as a fish pond with a water source that flows directly from the mountain. However, the lack of available human resources means that activities in this field do not run well. Apart from that, the lack of knowledge regarding aspects of cultivation is a fear for people to start moving in this field. The community empowerment activities in Gelarwangi Village through pomfret cultivation activities have several challenges that must be faced, such as the condition of the community which has difficulty buying fish food which can cause productivity to be less than optimal, the use of alternative feed that is not good and not suitable, production results that are difficult for the market to absorb. , fish prices tend to fluctuate, lack of public knowledge regarding three aspects of cultivation, such as hatching, nursery and enlargement, lack of understanding regarding feed nutrition, fish health, the environment and good cultivation methods. This activity will be carried out in Mei 2025 in Gelarwangi Village, Cidaun District, Cianjur Regency. This research uses a qualitative approach with a case study method to explore community economic empowerment. The case study method was chosen for its ability to provide an in-depth investigation of program dynamics, with a focus on experiences and wider impacts on local communities. Data was obtained using semi-structured interviews, document studies and field observations. The costs for pomfret cultivation activities are incurred by the village government with the aim of generating high income for the business carried out. The cost components incurred are fixed costs and variable costs, where fixed costs are around IDR 300.000,00 per month and variable costs are around IDR 500.000,00 The average amount of income received is around 17 million rupiah per group. And per person it is around IDR 560.000,00. Based on the research and analysis carried out, it was concluded that the average amount of income received in the 4 month production period was IDR 17.000.000,00, so that with this the community's economy, especially the Gentra Parahiangan Art Group, increased further.